The British Home Stores pension scheme: privatised looting?. Issue 4 (6th August 2019) - Clark, Ian
Abstract: On entering administration, British Home Stores owed its pension scheme £571 million—a significant employment relations issue of historical wage theft by investor–owner managers. The article locates 'lawful' looting of business assets in a framework that builds on Ackerlof and Romer's theory of bankruptcy for profit and connects this to an empirical narrative on business re‐structuring at British Home Stores towards administration.